Cover Feature: Near‐Infrared Phosphorescent Supramolecular Alkyl/Aryl‐Iridium Porphyrin Assemblies by Axial Coordination (Chem. Eur. J. 54/2018). Issue 54 (17th September 2018) - Qin, Lin; Guan, Xiangguo; Yang, Chen; Huang, Jie‐Sheng; Che, Chi‐Ming
Abstract : Ir(porphyrin)‐based supramolecular metallamacrocycles and metallacages were constructed stepwise through the axial coordination of Ir porphyrin building blocks (ball‐and‐stick representation) with various di‐ or tritopic diaryl or trialkyl ligands (represented by chains with green hexagonal buttons) and ditopic isocyanide or pyridine ligands (represented by chains with blue hexagonal buttons). These supramolecules (depicted as bright red fireworks in night sky) exhibit NIR emission with microsecond phosphorescence lifetimes. More information can be found in the Full Paper by C.‐M. Che, J.‐S. Huang, et al. onpage 14400 .